Acidic pH derived from cancer cells as a double‐edged knife modulates wound healing through DNA repair genes and autophagy. Issue 1 (11th November 2019) - Rabiee Motmaen, Shadi; Tavakol, Shima; Joghataei, Mohammad T.; Barati, Mahmoud
Abstract: Wound healing is a sequester program that involves diverse cell signalling cascades. Notwithstanding, complete signal transduction pathways underpinning acidic milieu derived from cancer cells is not clear, yet. MTT (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay, fluorescein diacetate/propidium iodide staining, and cell cycle flow cytometry revealed that acidic media decreased cell viability and cell number along with enhanced dead cells and S‐phase arrest in normal fibroblasts. Notably, the trends of intracellular reactive oxygen species production and lactate dehydrogenase release significantly increased with time. It seems the downregulation of Klf4 is in part due to acidosis‐induced DNA damage. It promoted cells towards S‐phase arrest and diminished cell proliferation. Klf4 downregulation had a direct correlation with the P53 level while acidic microenvironment promotes cells towards cell death mechanisms including apoptosis and autophagy. Noteworthily, the unchanged levels of Rb and Mlh1 indicated in those genes had no dominant role in the repairing of DNA damage in fibroblasts treated with the acidic microenvironment. Therefore, cells owing to not entering to mitosis and accumulation of DNA damage were undergone cell death to preserve cell homeostasis. Since acidic media decreased the level of tumour suppressor and DNA repair genes and altered the normal survival pathways in fibroblasts, caution should be exercised to not lead to cancer rather than wound healing.